The Concept of Ru'yat Al-Hilal According to Muhammad Quraish Shihab (Analytical Study of Q.S. Al-Baqarah: 185 in Tafsir Al-Misbah) - Abdul Muiz; Romy Furqani (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2024)
Islamic science and understanding, the concept of ru'yat al-Hilal is a complex and interesting discussion. Muslims often argue about the interpretation and application of ru'yat al-Hilal. Many scholars and scholars have different views. In-depth study of this concept is relevant and important. An  The problem raised in this study is how M. Quraish Shihab's interpretation of Ru'yat al-Hilal in QS. al-Baqarah and how the influence of M. Quraish Shihab's interpretation of Ru'yat al-Hilal on the current context. The purpose of this study is to find out M. Quraish Shihab's interpretation of Ru'yat al-Hilal in QS. al-Baqarah and to find out the influence of M. Quraish Shihab's interpretation of Ru'yat al-Hilal on the current context.The approach in this research is a qualitative type of literature (Library research), This involves data documentation activities through literature studies, especially related to the mufassir's views on ru'yat al-Hilal. The results of this study indicate that M. Quraish Shihab explained two important aspects related to ru'yat al-hilal in the verse, the first is that if someone has seen the moon with the naked eye, it is sufficient as a marker of the beginning of worship time. The second aspect he reveals is that the crescent moon acts as a timepiece both for humans and as an indication of the beginning of the time for the Hajj pilgrimage, because the time of worship is very important for Muslims.  These interpretations are very influential in determining the beginning of Ramadan, as is the case with the Muhammadiyah and NU (Nahdhatul Ulama) organizations to this day.